여러 가지 높이를 갖는 삼각형 구조 InGaAs/GaAs 양자세선 구조 성장 - 김성일; 김영환; 한일기 (한국재료학회, 2004)
InGaAs/GaAs quantum wire structures were grown by low pressure metalorganic chemical vapor deposition by using selective area epitaxy. In0.2Ga0.8As/GaAs quantum wire structures were grown on a SiO2 masked GaAs substrate. Quantum wire structures with sharp tips and smooth side walls were grown. We have grown InGaAs/GaAs quantum wire structures using variously opened width of the SiO2 mask. Even though the opening widths of SiO2 masked GaAs substrate were different, similar shapes of triangular structures were grown. Using various kinds of differently opened SiO2 masked area, it would be possible to grow quantum wire structures with various thicknesses. The quantum wire structures are formed near the pinnacle of the triangular structure. Therefore, the fabrication of the uniquely designed integrated optical devices which include light emitting sources of multiple wavelength is possible.